Some feature geology-geopohysical models of placer deposits of diamants - V Yu Abramov; V I Brovkin (RUDN Journal of Engineering Research, 2012)
Make an example a feature petrophysical property and geology-geophysical models of placer deposits of diamonds of North Ural. Make a effect mode of geological task determination with geophysical methods.